Методическая разработка по курсу "Программирование" - Валединский В. Д. Владимир Дмитриевич; Кушниренко А. Г. Анатолий Георгиевич; Лебедев Г. В. Геннадий Викторович; Размыслов Ю. П. Юрий Питиримович; Фоменко А. Т. Анатолий Тимофеевич; Скляренко Е. Г. Евгений Григорьевич; Голо В. Л. Войцлав Любомирович (Москва, Изд-во Московского ун-та, 1991)
Исключено из фонда НТБ ТПУ